FPGA-BASED DUAL SIMULTANEOUS SIGNAL GENERATOR USING REDUCED MEMORY DIRECT DIGITAL SYNTHESIS - Firmansyah, Iman (Teknologi Indonesia, 2013)
This paper describes the implementation of an FPGA (Field Programmable Gate Array)-based signal generator that simultaneously generates dual frequencies. The example demonstrates the capability of generating twodifferent frequencies at the same time. Direct Digital Synthesis or DDS is implemented as the core in generating the signal. To reduce the memory size, the quadrature symmetry of sine wave is created in order to achieve an effi cient look-up table for DDS core. As a result, only one fourth of total look-up table is allocated for storing the data. The system has been developed for Xilinx Spartan-6 XC6SLX9 FPGA integrated with 12-bit Pmod-AD1 analog to digital converter module consisting of AD7476A. The user sets the voltage input connected to Pmod-AD1 module as input control for changing the frequency; each input is dedicated to one channel of frequency. The system is also integrated with 8-bit Pmod-DA1 digital to analog converter module (AD7303) for generating the output signal. The advantage of parallelism capability in FPGA makes it possible to generate two different frequencies (2.18 KHz and 4.35 KHz) simultaneously.